Graduates' satisfaction with the Chilean basic education teacher training degree program. Issue 1 (26th July 2019) - Espinoza, Oscar; González, Luis; Sandoval, Luis; McGinn, Noel; Loyola, Javier; Castillo, Dante
Abstract : Purpose: The purpose of this paper is to improve future teacher training by assessment of university graduates' satisfaction with their preparation in Basic Education teaching. Design/methodology/approach: This descriptive study employed a self-administered survey questionnaire to a representative sample of 235 graduates between 2014 and 2016 from three universities in Chile. The questionnaire generated information about the graduates' background (age, gender, parents' education and prestige of secondary school attended); an evaluation of three dimensions of their degree program (instructional quality, infrastructure and employability), and experiences in the labor market (including salary). Analysis of variance was used to assess relationships between satisfaction, and other variables. Findings: In general, graduates were satisfied with all aspects of their training. Satisfaction levels were higher from those assumed to have lower expectations. Contrary to this hypothesis, university prestige is not directly related to satisfaction. Instead, expectations and employability moderate the effect of prestige. Research limitations/implications: The sample is not representative of the 59 universities in Chile nor of the many other degree programs offered in those universities. Practical implications: Program directors concerned about improving the public reputation or prestige of their program will benefit from efforts to improve the quality of the program and its infrastructure, and relevance for entrance into the world of work. Originality/value: This study provides information not previously available about graduate satisfaction in teaching degree programs in Chile.